Hypoplastic Posterior Leaflet Mitral Valve Associated with Bicuspid Aortic Valve - Velarde-Acosta, Kevin (2024)
Agenesis or hypoplasia of the posterior leaflet of the mitral valve (HPMVL) is a rare congenital anomaly, and its finding in adulthood is even more extraordinary because of the high morbidity and mortality generated in childhood. Its association with other congenital heart defects has been reported. We present a clinical case of an adult from the Andes with HPMVL associated with a bicuspid aortic valve (BAV)—which generated severe and moderate valvar regurgitation— who underwent successful surgery.